Polar winter climate change: strong local effects from sea ice loss, widespread consequences from warming seas - T. Naakka; D. Köhler; K. Nordling; K. Nordling; P. Räisänen; M. T. Lund; R. Makkonen; R. Makkonen; J. Merikanto; B. H. Samset; V. A. Sinclair; J. L. Thomas; et al. (Atmospheric Chemistry and Physics)
Decreasing sea ice cover and warming sea surface temperatures (SSTs) impact the climate at both poles in uncertain ways. We aim to reduce the uncertainty by comparing output of 41-year-long simulations from four atmospheric general circulation models (AGCMs). In our “Baseline” simulations, the models use identical prescribed SSTs and sea ice cover conditions representative of 1950–1969. In three sensitivity experiments, the SSTs and sea ice cover are individually and simultaneously changed to conditions representative of 2080–2099 in a strong warming scenario. Overall, the models agree that warmer SSTs have a widespread impact on 2 m temperature and precipitation, while decreasing sea ice cover mainly causes a local response (i.e. the greatest warming occurs where sea ice is perturbed). Thus, decreasing sea ice cover causes greater changes in precipitation and temperature than in warmer SSTs in areas where sea ice cover is reduced, while warmer SSTs dominate the response elsewhere. In general, the response in temperature and precipitation to simultaneous changes in SSTs and sea ice cover is approximately equal to the sum due to individual changes, except in areas of sea ice decrease where the joint effect is smaller than the sum of the individual effects. The models agree less well on the magnitude and spatial distribution of the response in mean sea level pressure; i.e. uncertainties associated with atmospheric circulation responses are greater than uncertainties associated with thermodynamic responses. Furthermore, the circulation response to decreasing sea ice cover is sometimes significantly enhanced but sometimes counteracted by the response to warmer SSTs.